1994
DOI: 10.1128/jb.176.2.333-337.1994
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies recombination between the penA genes of Neisseria meningitidis and commensal Neisseria species during the emergence of penicillin resistance in N. meningitidis: natural events and laboratory simulation

Abstract: The penicillin-binding protein 2 genes (penA) of penicillin-resistant Neisseria meningitidis have a mosaic structure that has arisen by the introduction of regions from the penA genes of Neisseria flavescens or Neisseria cinerea. Chromosomal DNA from both N. cinerea and N. flavescens could transform a penicillin-susceptible isolate of N. meningitidis to increased resistance to penicillin. With N. flavescens DNA, transformation to resistance was accompanied by the introduction of the N. flavescens penA gene, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
102
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(106 citation statements)
references
References 16 publications
(25 reference statements)
4
102
0
Order By: Relevance
“…After their introduction into N. meningitidis, by horizontal acquisition or by mutations, both types of sulfonamide resistance genes have spread among meningococci of different serogroups and serotypes under selective pressure from the frequent use of sulfonamides. The intraspecies transfer of genetic material has earlier been shown to result in hybrid penicillinbinding proteins encoding low levels of penicillin resistance (3). In this case the origin of the foreign DNA was shown to be two Neisseria commensal species, N. flavescens and N. cinerea (3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…After their introduction into N. meningitidis, by horizontal acquisition or by mutations, both types of sulfonamide resistance genes have spread among meningococci of different serogroups and serotypes under selective pressure from the frequent use of sulfonamides. The intraspecies transfer of genetic material has earlier been shown to result in hybrid penicillinbinding proteins encoding low levels of penicillin resistance (3). In this case the origin of the foreign DNA was shown to be two Neisseria commensal species, N. flavescens and N. cinerea (3).…”
Section: Discussionmentioning
confidence: 97%
“…This points to the possibility of interspecies transfer and the exchange of DNA among related bacteria. In parallel, the penA gene, encoding the penicillin-binding protein 2, in meningococcal strains with increased levels of resistance to penicillin was found to have mosaic structures with regions identical to those of the corresponding parts of the penA gene in Neisseria flavescens and Neisseria cinerea (3).…”
Section: Site-directed Mutagenesis Of the Meningococcal Dhps Genementioning
confidence: 98%
“…N. meningitidis is naturally competent for transformation, which enables the horizontal transfer of DNA between strains, resulting in mosaic structures at genetic loci and a highly diverse meningococcal population (13,14). The penA gene is altered as a result of DNA transfer between meningococcal strains or from commensal Neisseria species (15)(16)(17)(18). We previously developed a rapid approach to define meningococcal penA alleles based on restriction fragment length polymorphism (RFLP).…”
mentioning
confidence: 99%
“…Molecular studies have shown that many chromosomal genes from bacteria have a mosaic pattern (2,5,15,19) presumably as a result of recombination with DNA from heterologous sources (10,30,31). The mechanisms causing these patterns are, however, seldom known.…”
mentioning
confidence: 99%